Innate and adaptive immunity to the nematode Strongyloides stercoralis in a mouse model - Bonne-Année, Sandra (Immunol Res, 2011)
Mice have been used to the study the mechanisms of protective innate and adaptive immunity to larval S. stercoralis. During primary infection neutrophils and eosinophils are attracted by parasite components and kill the larvae by release of granule products. Eosinophils also function as antigen presenting cells for the induction of a Th2 response. B-cells produce both IgM and IgG that collaborate with neutrophils to kill worms in the adaptive immune response. Vaccine studies have identified a recombinant diagnostic antigen that induced high levels of immunity to infection with S. stercoralis in mice. These studies demonstrate that there are redundancies in the mechanisms used by the immune response to kill the parasite and that a vaccine with a single antigen may be suitable as a prophylactic vaccine to prevent human strongyloidiasis.